What type of client do you need? The brand value co-creation in the banking sector - Peña-García, Nathalie; Losada-Otálora, Mauricio; Juliao-Rossi, Jorge (Frontiers in Psychology, 2022)
Service-dominant logic established that for the success of service industries, it is vital to acknowledge the customer as an active agent in the commercial ecosystem. To carry it out, the consumer must participate in value creation. This study aims to find the key customer-based factors that influence the brand value co-creation process in the banking sector, analyzing the dynamics in different customers across national cultures and idiosyncrasies. In this paper, we analyze the potential heterogeneous idiosyncrasy of customers and how it leads to becoming more engaged in the co-creation process. First, a quantitative investigation was carried out in the United States, Mexico, Spain, Argentina, and Brazil, obtaining a total of 2029 valid questionnaires where latent profile analyses and ANOVAs were performed to identify and describe the latent profiles of consumers co-creators of brand value. Afterward, a PLS-SEM was performed to test the research model in each segment. The results show four different profiles of customer co-creators of brand value, from non-co-creators (detractors), skeptical and neutral, to customers committed to co-creating brand value with their banks. The results indicate that detractor customers lack the motivations and resources to carry out co-creation behaviors. On the other hand, creativity and connectedness were crucial for customers co-creators of value. To the authors' understanding, no studies have used latent segmentation to find the profiles of customer co-creators of brand value. Furthermore, the study has been carried out in different countries to observe the effect of idiosyncrasy and national culture on customer behavior.